Pengaruh Media Puzzle Stick Terhadap Kreativitas Anak Usia 4-5 Tahun di TK Multazam - Nur Fitri Maharani; Muhammad Akil Musi; Azizah Amal (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
The central problem of this study is the creativity of children aged 4-5 years at Multazam Kindergarten. The children consistently demonstrate a tendency to await instructions from their teachers whenever they engage in the construction of toys or other activities. Their objective is to emulate existing practices rather than to devise novel ones. The objective of this study is to ascertain the impact of Puzzle Stick Media on the creativity of children aged four to five at Multazam Kindergarten in Gowa Regency. The research approach employed is a quantitative approach, with the type of research Quasi-Experimental Design. The population of this study comprised 30 children aged 5-6 years at Mekar Sari Palampang Kindergarten. The sampling method employed in this study was purposive sampling. The sample in this study consisted of 12 children, 6 children as the experimental group and 6 children as the control group. The data collection technique employed in this study is descriptive statistical analysis and non-parametric statistical analysis using the Wilcoxon Sign Rank Test. The findings of the study indicate that the creativity of children in the experimental group who participated in play activities involving puzzle stick media demonstrated superiority in comparison to the control group. The findings of the data analysis demonstrated a mean increase of 29.67 in the experimental group, while the control group exhibited a mean increase of 18.83. The statistical significance of these results is indicated by the p-value. In the event that the two-tailed test result is less than 0.027 and greater than or equal to 0.05, the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. Therefore, it can be concluded that puzzle stick media exerts a significant effect on the creativity of children aged 4-5 years at Multazam Kindergarten, Gowa Regency.